2019
DOI: 10.9779/puje.2018.234
|View full text |Cite
|
Sign up to set email alerts
|

School Engagement as a Predictor of Burnout in University Students

Abstract: The aim of this study is to examine the relationship between school engagement and burnout of university students. The research employs relational survey model and the participants are 472 students studying at a public university in Ankara in Turkey. The data collection tools were "The Maslach Burnout Inventory-Student Survey" and "University Student Engagement Inventory". The findings of the research show that the relationship between university students' school engagement and emotional exhaustion, cynicism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
5
9
0
2
Order By: Relevance
“…School participation had a statistically significant effect on intention to persist in vocational education. This result is consistent with those of Akbaşli, Arastaman, Gün, and Turabik (2019). The authors conducted a study of the relationship between school engagement and burnout (exhaustion) with 472 Turkish university students.…”
Section: Discussionsupporting
confidence: 88%
“…School participation had a statistically significant effect on intention to persist in vocational education. This result is consistent with those of Akbaşli, Arastaman, Gün, and Turabik (2019). The authors conducted a study of the relationship between school engagement and burnout (exhaustion) with 472 Turkish university students.…”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that the highest mean score obtained by the students for personality traits was agreeableness while the lowest was neuroticism, which was also supported by some other studies (Burke & Witt, 2004;Côté & Moskowitz, 1998;Jensen & Patel, 2011;Saling et al, 2019;Templer, 2012). On the other hand, levels of engagement and all dimensions of burnout were moderate among the participants, as also reported by Akbaşlı et al (2019).…”
Section: Discussionsupporting
confidence: 74%
“…It is expected that the individuals' study habits and engagement levels are also affected by their personality traits. Especially in Turkey, although a few researchers investigated the relationship between burnout and engagement (e.g., Akbaşlı et al, 2019;Bilge et al, 2014), to the best of our knowledge, there are no studies examining these concepts (i.e., burnout and engagement) with personality traits and students' academic achievement together.…”
Section: Personality Traitsmentioning
confidence: 99%
“…Okul tükenmişliği ile ilgili yapılan literatür araştırmasında ölçek geliştirme-uyarlama çalışmaları (Aypay, 2011;Çapri, Gündüz ve Gökçakan, 2011) Türkiye'de üniversite öğrencilerinin okul tükenmişliğini incelemeye yönelik çalışmalar (Akbaşlı, Arastaman, Gün & Turabik, 2019;Çam, Deniz ve Kurnaz, 2014;Gündüz, Çapri ve Gökçakan, 2012;Küçüksüleymanoğlu ve Eğilmez, 2013;Ören ve Türkoğlu,2006;Özgen, 2016;Seçer, 2015;Seçer, 2015a;Tansel, 2015) ve Lise öğrencilerinin okul tükenmişliğini inceleyen çalışmalar (Atik, Özer ve Karadağ, 2018;Avara, 2015;Aypay ve Eryılmaz, 2011;Aypay ve Eryılmaz, 2011a;Aypay ve Sever, 2015;Çakır, 2015;Eker, 2007;Koçak ve Secer, 2018;Kutsal, 2009;Kutsal ve Bilge, 2012; Seçer ve Gençdoğan, 2012) olduğu görülmektedir.…”
Section: Introductionunclassified